Phylogeography of the Lacerta viridis complex: mitochondrial and nuclear markers provide taxonomic insights. (11th January 2016) - Marzahn, Ellen; Mayer, Werner; Joger, Ulrich; Ilgaz, Çetin; Jablonski, Daniel; Kindler, Carolin; Kumlutaş, Yusuf; Nistri, Annamaria; Schneeweiss, Norbert; Vamberger, Melita; Žagar, Anamarija; Fritz, Uwe
Abstract: Based on broad, nearly rangewide sampling, we reanalysed the phylogeography of the Lacerta viridis complex using the mitochondrial cytochrome b gene and the intron 7 of the nuclear β ‐fibrinogen gene. Using the mitochondrial marker, we identified in phylogenetic analyses 10 terminal clades clustering in four deeply divergent main lineages whose relationships are weakly resolved. These lineages correspond to Lacerta bilineata, L. viridis, the previously identified Adriatic or West Balkan lineage and a newly discovered fourth lineage from the Anatolian Black Sea coast and the south‐eastern Balkan Peninsula. Except for the latter lineage, there is considerable phylogeographic structuring in each lineage, with higher diversity in the south of the distribution ranges. This pattern indicates the existence of two distinct microrefugia in the Italian Peninsula and Sicily and of up to seven microrefugia in the Balkan Peninsula, but of only one refugium along the Black Sea coast of Anatolia. We identified secondary contact zones of the main lineages and of terminal clades within these lineages. However, most of the formerly described putative contact zone of L. bilineata and L. viridis turned out to be a contact zone between the Adriatic lineage and L. viridis, but L. bilineata seems to be involved only marginally. Our nuclear marker could not unambiguously resolve whether there is gene flow in contact zones. Thus, further research is necessary to decide whether the four main lineages are conspecific or whether they represent distinct biological species. We restrict the name L. v. meridionalis to the newly identified genetic lineage from Turkey and south‐eastern Europe, synonymize some previously recognized taxa and suggest a tentative nomenclature for the L. viridis complex. Abstract : We identified in the Lacerta viridis complex 10 terminal mitochondrial clades clustering in four deeply divergent lineages, corresponding to L. bilineata, L. viridis, the Adriatic or West Balkan lineage and a newly discovered fourth lineage (Anatolian Black Sea coast, southeastern Balkan Peninsula). We identified several secondary contact zones of the main lineages and terminal clades. However, most of the formerly described contact zone of L. bilineata and L. viridis turned out to be a contact zone between the Adriatic lineage and L. viridis . It remains unclear whether there is gene flow in contact zones.